Carbones as Ligands in Novel Main‐Group Compounds E[C(NHC)2]2 (E=Be, B+, C2+, N3+, Mg, Al+, Si2+, P3+): A Theoretical Study. Issue 14 (15th February 2017) - Hermann, Markus; Frenking, Gernot
Abstract: Quantum chemical calculations of the main‐group compounds E[C(NHC Me )2 ]2 (E=Be, B +, C 2+, N 3+, Mg, Al +, Si 2+, P 3+ ) have been carried out using density functional theory at the BP86/def2‐TZVPP and BP86‐D3(BJ)/def2‐TZVPP levels of theory. The geometry optimization at BP86/def2‐TZVPP gives equilibrium structures with two‐coordinated species E and bending angles C‐E‐C between 152.5° (E=Be) and 110.5° (E=Al). Inclusion of dispersion forces at BP86‐D3(BJ)/def2‐TZVPP yields a three‐coordinated beryllium compound Be[C(NHC Me )2 ]2 as the only energy minimum form. Three‐coordinated isomers are found besides the two‐coordinated energy minima for the boron and carbon cations B[C(NHC Me )2 ]2 + and C[C(NHC Me )2 ]2 2+ . The three‐coordinated form of the boron compound is energetically lower lying than the two‐coordinated form, while the opposite trend is calculated for the carbon species. The theoretically predicted bond dissociation energies suggest that all compounds are viable species for experimental studies. The X‐ray structure of the benzoannelated homologue of P[C(NHC Me )2 ]2 3+ that was recently reported by Dordevic et al. agrees quite well with the calculated geometry of the molecule. A detailed bonding analysis using charge and energy decomposition methods shows that the two‐coordinated neutral compounds Be[C(NHC Me )2 ]2 and Mg[C(NHC Me )2 ]2 possess strongly positively charged atoms Be and Mg. The carbodicarbene groups C(NHC Me )2 serve as acceptor ligands in the compounds and may be sketched with dative bonds (NHC Me )2 C←E→C(NHC Me )2 (E=Be, Mg). Dative bonds in which the carbones C(NHC Me )2 are donor ligands are suggested for the cations (NHC Me )2 C→E←C(NHC Me )2 (E=B +, Al + ). The dications and trications possess electron‐sharing bonds in which the bonding situation is best described with the formula [(NHC Me )2 C] + ‐E‐[C(NHC Me )2 ] + (E=C, Si, N +, P + ). Abstract : How do carbones bond as ligands? Carbones (CL2 ) are four‐electron donors that exhibit specific double Lewis base properties. Calculations of complexes E[C(NHC)2 ]2 (E=Be, B +, C 2+, N 3+, Mg, Al +, Si 2+, P 3+ ) with carbodicarbenes C(NHC)2 as ligands suggest that the optimized species are promising targets for synthesis, the trication P[C(NHC)2 ]2 3+ of which has recently been isolated.